2011
DOI: 10.1080/00380768.2011.637305
|View full text |Cite
|
Sign up to set email alerts
|

Rice phenolics efflux transporter 2 (PEZ2) plays an important role in solubilizing apoplasmic iron

Abstract: Iron (Fe) is an essential micronutrient for plants; however, despite its abundance in soils it is not readily available in neutral to alkaline soils. Plants secrete phenolics, such as protocatechuic acid (PCA) and caffeic acid (CA), to absorb and utilize precipitated apoplasmic Fe from root surfaces. However, the synthesis and secretion of phenolics have not been well characterized in plants. We have identified and characterized a rice (Oryza sativa L.) mutant with reduced amounts of PCA and CA in xylem sap an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 44 publications
0
62
0
Order By: Relevance
“…These results suggest that metal translocation was aberrant in TOM2 RNAi plants. Previously, phenolics efflux zero 1 and 2 (PEZ1 and PEZ2), the efflux transporters of protocatechuic acid, have been reported to contribute to the long-distance transport of iron through the solubilization of precipitated apoplasmic iron in the root xylem (58,59), suggesting that some transporters are necessary to mobilize metals accumulated in the apoplasm to transport them to sinks in plants.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that metal translocation was aberrant in TOM2 RNAi plants. Previously, phenolics efflux zero 1 and 2 (PEZ1 and PEZ2), the efflux transporters of protocatechuic acid, have been reported to contribute to the long-distance transport of iron through the solubilization of precipitated apoplasmic iron in the root xylem (58,59), suggesting that some transporters are necessary to mobilize metals accumulated in the apoplasm to transport them to sinks in plants.…”
Section: Discussionmentioning
confidence: 99%
“…However, under certain conditions Fe is not readily available, and Fe is difficult to mobilize; thus, Fe stored in the plant needs to be reutilized. For example, phenolics are secreted to remobilize the root apoplastic Fe and improve Fe nutrition in red clover (Trifolium pratense) and rice (Oryza sativa) (Jin et al, 2007;Bashir et al, 2011). Moreover, Lei et al (2014) reported that the cell wall can be an important Fe source during periods of limited Fe supply.…”
mentioning
confidence: 99%
“…For GSH uptake experiments oocytes of Xenopus laevis frogs were injected with either capped complementary RNA encoding OsOPT7 or water and incubated at 17 °C for 48 h (Kato et al 2001). Then oocytes were placed in Barth-MES; pH 5, 6 or 7) containing 100 µM GSH, (20 nM 3 H-labeled GSH) After 10 h incubation, oocytes were washed with 100 µl Barth-MES solution, followed by the addition of 100 µl of 10 % SDS, vortexed briefly and radioactivity of the oocytes was measured in a liquid scintillation analyzer as described previously Bashir et al 2011b). For NA and DMA transport experiments, OsOPT7 was cloned into pGEM-3zf(+) vector and substrate transport activity for NA and DMA was measured in oocytes at −80 and −100 mV, as described previously (Koike et al 2004).…”
Section: Gsh Transport Assaymentioning
confidence: 99%
“…The genes involved in MA biosynthesis have been characterized, and most of these genes are regulated by the Fe status of plants Lingam et al 2011;Kobayashi and Nishizawa 2012;Bashir et al 2010). After acquisition from soil, Fe is transported to leaves and developing seeds through a complex and complicated molecular mechanisms (Bashir et al 2013a;Ishimaru et al 2011b;Bashir et al 2011b;Yokosho et al 2009;Yamaji and Ma 2014). Moreover, cellular distribution of Fe is also very important and disturbance in cellular Fe homeostasis results in significant alteration in cellular metabolism (Bashir et al , c, 2013bKim et al 2006;Nozoye et al 2014a, b;Zhang et al 2012).…”
Section: Introductionmentioning
confidence: 95%